Initial characterization of a transgenic mouse with overexpression of the human D1-dopamine receptor in the heart - Lina Maria Rayo Abella; Hannes Jacob; Christin Hesse; Britt Hofmann; Sarah Schneider; Lisa Schindler; Max Keller; Igor B. Buchwalow; CongYu Jin; Pertti Panula; Stefan Dhein; Jan Klimas; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Dopamine can exert effects in the mammalian heart via five different dopamine receptors. There is controversy whether dopamine receptors increase contractility in the human heart. Therefore, we have generated mice that overexpress the human D 1 -dopamine receptor in the heart (D 1 -TG) and hypothesized that dopamine increases force of contraction and beating rate compared to wild-type mice (WT). In D 1 -TG hearts, we ascertained the presence of D 1 -dopamine receptors by autoradiography using [ 3 H]SKF 38393. The mRNA for human D 1 -dopamine receptors was present in D 1 -TG hearts and absent in WT. We detected by in-situ-hybridization mRNA for D 1 -dopamine receptors in atrial and ventricular D 1 -TG cardiomyocytes compared to WT but also in human atrial preparations. We noted that in the presence of 10 µM propranolol (to antagonize β-adrenoceptors), dopamine alone and the D 1 - and D 5 -dopamine receptor agonist SKF 38393 (0.1–10 µM cumulatively applied) exerted concentration- and time-dependent positive inotropic effects and positive chronotropic effects in left or right atrial preparations from D 1 -TG. The positive inotropic effects of SKF 38393 in left atrial preparations from D 1 -TG led to an increased rate of relaxation and accompanied by and probably caused by an augmented phosphorylation state of the inhibitory subunit of troponin. In the presence of 0.4 µM propranolol, 1 µM dopamine could increase left ventricular force of contraction in isolated perfused hearts from D 1 -TG. In this model, we have demonstrated a positive inotropic and chronotropic effect of dopamine. Thus, in principle, the human D 1 -dopamine receptor can couple to contractility in the mammalian heart.